Validity of Wagner, SINBAB, PEDIS, and WIFI Scoring Systems to Assess Risk of Amputation in Patients with Diabetic Foot Ulcers - Gunawan, I Made Kasmadi; Budiarta, Ida Bagus; Mahadewa, Tjokorda Gde Bagus; Suryawisesa, Ida Bagus Made; Wibawa, I Gusti Agung Bagus Krisna; Ariyanta, Kadek Deddy (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): JBN (Jurnal Bedah Nasional), 2024)
Aim: This study aims to determine validity of the Wagner, SINBAD, PEDIS, and WIFI scoring systems in assessing the risk of amputation in patients with diabetic foot ulcers at Prof. dr. I.G.N.G. Ngoerah General Hospital, Denpasar. Methods: This research is an observational study of diagnostic tests with a cross-sectional design. The sample in this study was selected by consecutive sampling from 1 January 2022 to 31 December 2022 with total of 72 respondents. Results: Wagner score test obtained sensitivity 77.2%, specificity 80.0%, PPV 93.6%, NPV 48%, accuracy 77.7%, and RR 1.8. PEDIS score test results obtained sensitivity 82.5%, specificity 86.7%, PPV 95.9%, NPV 56.5%, accuracy 83.3%, and RR 2.2. The results of the SINBAD test score obtained sensitivity 78.9%, specificity 66.7%, PPV 90.0%, NPV 45.5%, accuracy 76.3%, and RR 1.6. WIFI score test obtained sensitivity 89.5%, specificity 66.7%, PPV 91.1%, NPV 62.5%, accuracy 84.7%, and RR 2.4. Conclusion: The WIFI score has better sensitivity and accuracy compared to score Wagner, SINBAD, and PEDIS so it is recommended to use the WIFI score to assess the risk of amputation in diabetic foot ulcer patients.